Integrated transcriptome, GWAS, and metabolome revealed the mechanism of seed germination in sorghum - Ju, Lan; Liu, Ruizhen; Cheng, Xiaoqiang; Wang, Yao; Lv, Xin; Chu, Jianqiang; Niu, Hao; Yan, Haisheng; Wang, Yubin; Fan, Fangfang; Ping, Junai (Frontiers in Plant Science, 2025)
IntroductionIn sorghum production, pre-harvest sprouting (PHS) is one of the most important problems, and the primary cause of sprouting susceptibility is a low dormancy prior to crop harvest.MethodsTo cope with this situation, we conducted transcriptome, metabolome, and genome-wide association studies (GWAS) to understand the mechanism underlying sorghum seed dormancy and germination.ResultsWe constructed 36 transcriptome libraries from four sorghum materials with contrasting germination abilities at three developmental stages. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis based on transcriptome data showed that metabolic pathways, biosynthesis of secondary metabolites, starch and sucrose metabolism, and plant hormone signal transduction are greatly enriched. In plant hormone signal transduction, genes associated with abscisic acid (ABA), gibberellic acid (GA), brassinosteroid (BR), and the auxin signaling pathway are involved in seed germination. GWAS of the 24-h germination rate across 232 cultivars identified four significant SNPs and 31 candidate genes, with SbPP2C33 emerging as the top candidate based on transcriptome integration. Combining transcriptome and metabolome analyses revealed that genes facilitating starch/sucrose conversion to glucose, fructose, and maltose were upregulated in low-dormancy genotypes, consistent with the accumulation levels of corresponding metabolites.DiscussionIn summary, our findings demonstrate that ABA signaling, mediated by SbPP2C33, coordinates carbohydrate mobilization during seed germination in sorghum. These findings provide novel mechanistic insights into the hormonal regulation of metabolic processes in cereal crops.